2020
DOI: 10.33260/zictjournal.v4i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Devices in supporting members’ participation to Village Community Banks: The Design Thinking Approach

Abstract: Village Community Banks (VICOBA) and mobile phones have become assistance to many rural societies in encountering financial problems. However, mobile phone usages to VICOBA are isolated resulting in unsubstantial benefits that do not foster member’s participation. The weak participation of members to Village Community Banks activities has been one of the major impediments to their success despite owning of mobile devices to some members. The paper applies design thinking approach to explore the situation throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The use of digital application will improve market outreach through selling and buying of the stock market products. This also was observed by Gomera & Oreku, (2020) application of mobile technology increases customer participation in business. Electronic platform should be able to meet sellers and buyers to affect exchange online In a global market investor interacts with the world trough business transactions, therefore the need of such securities is inevitable.…”
Section: The Strategies To Tackle the Challenge Of Information In Sto...mentioning
confidence: 55%
See 1 more Smart Citation
“…The use of digital application will improve market outreach through selling and buying of the stock market products. This also was observed by Gomera & Oreku, (2020) application of mobile technology increases customer participation in business. Electronic platform should be able to meet sellers and buyers to affect exchange online In a global market investor interacts with the world trough business transactions, therefore the need of such securities is inevitable.…”
Section: The Strategies To Tackle the Challenge Of Information In Sto...mentioning
confidence: 55%
“…Therefore, using digital application will improve market outreach through selling and buying of the stock market products. This also was observed by Gomera & Oreku, (2020) application of mobile technology increases customer participation in business In a modern stock market, participants are allowed to purchase and sale their share through the platform without meeting for exchange. Arrangement for settlement is also done online by custodians which is arranged by the two counterparties.…”
Section: Practical Effects Of the Differences In The Information Betw...mentioning
confidence: 76%
“…"Formal credit and savings institutions for the poor have also been around for decades. They have been providing customers who were traditionally vacated by commercial banks a way to obtain financial services through cooperatives and development finance institutions" [2,[3][4][5][6][7][8][9][10][11]. "In the 1800s, various types of larger and more formal savings and credit institutions began to emerge in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Mwaipopo and Dauda (2019) contended that VICOBA promoted the accessibility of microcredit for the majority of women in Tanzania and hence they catalyzed women empowerment, despite no empirical data that validated their argument. Gomera and Oreku (2020) found that the use of ICT in promoting the performance of VICOBA was insufficient. However, this study did not assess how the use of ICT promoted women empowerment of the VICOBA clients.…”
Section: Introductionmentioning
confidence: 99%